AUTOMATION OF DUPLEX MILLING MACHINE BY USING PLC - Asst Prof Pallavi Bile (International Journal of Innovations in Engineering Research and Technology, 2022)
In the competitive market requires the special skills and technology. Especially cost cutting and control of overheads has become an prime necessity. Man power control and man power reduction has become common in these slowdown. Our project deals with such a concept which saves a labour cost and increases the operator efficiency. On similar ground we are going to manufacture duplex milling machine by using PLC To reduce the operators fatigue and improve productivity it was decide to design and manufacturing special purpose milling machine in which both side milling of cylindrical rod takes place. Milling process removes material from the work piece by advancing tool into work piece duplex milling machine is special type of machine. The type of cutters and shop formulas for setting up each operation safely plays a critical part in any operation involving power equipment. This also includes products for maintaining and proper setting up the work and methods of selecting various tools and object holding devices to get a job done safely without cursing damage to the equipment yourself or someone nearby. In conventional machine such as lathe machine both side milling requires large time for manufacturing as we have to hold work piece twice and surface finish is also moderate. So we are manufacturing duplex milling machine in which at a time both side face milling takes place and also surface finish is also very good